Beyond the basics: A qualitative exploration of mathematics teaching effectiveness in South African secondary schools - Oratilwe Penwell Mokoena; Solly Matshonisa Seeletse (Primatika)
In the world of teaching mathematics, significant disparities persist in teaching effectiveness and the interventions employed by educators. This study investigates the challenges faced by mathematics teachers and explores interventions to enhance learner performance. Through a qualitative research design, seven dedicated mathematics teachers were sampled using a purposive snowball sampling approach. Data were gathered through structured interviews with participants from selected secondary schools in the Madibeng Local Municipality. The study findings underpin the hurdles teachers encounter, including insufficient resources, congested annual teaching plans, demotivated learners, ill-discipline, and subject coercion. These issues are further compounded by the broader educational inequalities in the South African education system, a legacy of its fragmented and unequal education system inherited from the apartheid dispensation. Despite these challenges, government schoolteachers adopted effective strategies such as scaffolding, weekly assessments, the use of past exam papers, and learner-centered approaches. The study concludes that to enhance teaching effectiveness, teachers need robust support and adequate resources. Additionally, government bodies, school heads of departments, and principals must effectively collaborate to provide these necessary support and resources, thereby improving learner outcomes and reducing dropout rates. This study contributes invaluable insights into the complexities of teaching mathematics, highlighting effective practices and interventions to keep learners engaged and prevent them from swaying away to mathematical literacy or leaving school altogether.